The association between perceived neighborhood social cohesion and incident hypertension among older adults in the US Health and Retirement Study - Roma Dhingra; Kosuke Tamura; Tiffany M Powell-Wiley; Allana T Forde (American Journal of Epidemiology, 2026)
Abstract Background: Despite the association between lower perceived neighborhood social cohesion (PNSC) and higher risk of hypertension, there is limited research on this relationship. This population-based study examined the association between PNSC and incident hypertension among a nationally representative population of older adults across racial and/or ethnic groups and sex. Methods: Data were obtained from 2,998 US older adult participants (mean age=62.5 years, SD=8.12) from the Health and Retirement Study. Normotensive participants at baseline (2006 or 2008) were assessed for hypertension incidence at 4- and 8-year follow-up visits. PNSC was classified into tertiles. Weighted Cox proportional hazards regression was used to estimate the association between PNSC and incident hypertension. Interaction terms (PNSC and racial and/or ethnic group, PNSC and sex) were included in models adjusted for appropriate covariates (sex, racial and/or ethnic group, education, body mass index, alcohol use, cigarette smoking status), and models were stratified by racial and/or ethnic group and sex. Results: Overall, 40.5% of the study population developed hypertension. Low perceived neighborhood social cohesion (versus high) was associated with increased hypertension risk (HR=1.22, 95% CI: 1.08-1.37). This association was the strongest among Black adults (HR=2.28, 95% CI: 1.23-4.25) and Black females (HR=3.40, 95% CI: 1.34-8.62), though the interaction terms were not statistically significant (p-values for interaction >0.05). Conclusions: Individuals perceiving low neighborhood social cohesion may have increased hypertension risk, particularly among Black females. Future studies could test potential underlying mechanisms that explain this association and implement community-based interventions promoting cohesive communities as a potential strategy for reducing disparities in hypertension risk.